Observations on the development of the febrile response to pyrogen in newborn pigs - Moraes, R. N.; Macari, Marcos [UNESP]; Pela, I. R. (Karger Publishers, 1985)
The febrile response of newborn pigs to exogenous pyrogen injection was investigated. Lipopolysacharides (LPS, E coli) were injected intravenously into the superior vena cava of 1-30-day-old piglets. All the experiments were carried out in littermates half of which were injected with pyrogen and half with pyrogen-free saline. Newborn pigs did not develop a febrile response from 1 to 4 days of age; however, when the animals were 5 days old exogenous pyrogen determined a typical monophasic febrile response. A second intravenous injection of pyrogen into newborn pigs (1 day old) 24 h after the first did not raise body temperature. It is suggested that newborn pigs behave like the newborn of other mammalian species regarding endotoxin-induced thermogenesis.
Keywords: endotoxin; lipopolysaccharide; pyrogen; animal experiment; fever; newborn; nonhuman; priority journal; swine; thermogenesis; Aging; Animal; Animals, Newborn; Escherichia coli; Fever; Kinetics; Lipopolysaccharides; Support, Non-U.S. Gov't; Swine